Molecular Evolution of Slow and Quick Anion Channels (SLACs and QUACs/ALMTs) - Dreyer, Ingo; Gomez-Porras, Judith L.; Riaño Pachón, Diego Mauricio; Hedrich, Rainer; Geiger, Dietmar (Frontiers in Plant Science, 2012)
Electrophysiological analyses conducted about 25 years ago detected two types of anion channels in the plasma membrane of guard cells. One type of channel responds slowly to changes in membrane voltage while the other responds quickly. Consequently, they were named SLAC, for SLow Anion Channel, and QUAC, for QUick Anion Channel. Recently, genes SLAC1 and QUAC1/ALMT12, underlying the two different anion current components, could be identified in the model plant Arabidopsis thaliana. Expression of the gene products in Xenopus oocytes confirmed the quick and slow current kinetics. In this study we provide an overview on our current knowledge on slow and quick anion channels in plants and analyze the molecular evolution of ALMT/QUAC-like and SLAC-like channels. We discovered fingerprints that allow screening databases for these channel types and were able to identify 192 (177 non-redundant) SLAC-like and 422 (402 non-redundant) ALMT/QUAC-like proteins in the fully sequenced genomes of 32 plant species. Phylogenetic analyses provided new insights into the molecular evolution of these channel types. We also combined sequence alignment and clustering with predictions of protein features, leading to the identification of known conserved phosphorylation sites in SLAC1-like channels along with potential sites that have not been yet experimentally confirmed. Using a similar strategy to analyze the hydropathicity of ALMT/QUAC-like channels, we propose a modified topology with additional transmembrane regions that integrates structure and function of these membrane proteins. Our results suggest that cross-referencing phylogenetic analyses with position-specific protein properties and functional data could be a very powerful tool for genome research approaches in general.